Estudo petrográfico e mineralógico por MEV-EDS dos granitoides da mina da Serveng, pertencentes a Suíte Rosário - noroeste do Estado do Maranhão - PEREIRA, Lucas Yan de Oliveira (2020)
The Rosário Suite is a batolith formed by a set of paleoproterozoic-aged granite plutons (2.08 - 2.17 Ga) of tonalitic and granodioritic composition originated from an extensive calcium-alkaline affinity magmatism. They are exposed in tectono-erosive windows in the city of Rosario (Maranhão) 70Km south of São Luís. The suite is part of a cratonic nucleus called São Luís Craton, which represents a fragment of the West African Craton left on the South American Platform. after the opening of the Atlantic Ocean during the fragmentation of the Pangea Supercontinent. These are massive, leucocratic and holocrystalline rocks with predominantly coarse particle size. This work has as objective the petrographic and mineralogical study of the Rosário Suite rocks, and relate them with their use for crushed stone production in the region. For this, petrographic analyzes were performed under optical microscope through thin slides of three samples that vary their compositions between tonalitic and dioritic quartz, with the main mineralogy composed by plagioclase, quartz, amphibole. Semi-quantitative punctual chemical analyzes were also performed with SEM-EDS in polished lamina, providing a clearer picture of the mineralogical composition of the Rosario Suite rocks, such as the sodic nature of the plagioclase and the amphibole calcic.